Investing intangible assets in a modern economy - Zh. P. Samokhvalova (Путеводитель предпринимателя, 2023)
The development of small enterprises is an urgent economic task at the present stage. The support provided by the Government of the country, the decisions taken by the Central Bank are aimed at creating the foundations for the development of small businesses, but the conditions in which business has had to develop in recent years have severely affected the financial capabilities of existing and potential entrepreneurs. During this period, the structure of the types of activities that small and medium–sized businesses are engaged in has changed significantly. A sharp restriction in investment opportunities forces us to look for new forms with which to open or reformat existing small businesses. The use of an investment mechanism based on intangible assets in the form of a license agreement in the form of franchising will solve these issues. The use of a franchise is associated with certain difficulties, resulting in risks both arising in the process of formation and in the case of a developed and functioning business. Despite the rather specific risks in this area, the franchising market is developing quite dynamically, and although its development takes place in waves, sensitively reacting to the political situation, the development is progressive. The decline in the presence of foreign franchises on the Russian market was replaced by an increase in the import of Russian franchises to the previously non–existent markets of Turkey and the UAE. The innovation market, which includes the franchising market, as an integral part of intangible assets, is recognized as the most promising from the point of view of economic development.